Features pharmacotherapy of Diabetes Mellitus II type - Tryshchuk, N (Annals of Mechnikov’s Institute, 2020)
Epidemiological increased incidence of diabetes mellitus is still ongoing. Treatment of patients with diabetes mellitus is challenging due to several factors: low level of diagnostics, difficulties in choice of drugs, the limited use of self-monitoring of glucose by patients, clinical failure medicines. Article defines the main groups of drugs that are needed for the treatment of diabetes mellitus type 2, based on the mechanism of action, dosage, side effects, contraindications and applications of algorithms. These articles will help to rationally choose hypoglycemic drugs for patients with diabetes mellitus type 2, thereby improving the condition of diabetics and reducing the risk of complications.